Inadequate Models of Stereochemistry Based on Kimball’s Spheres and Pauli’s Exclusion Principle - Christian K. Jørgensen (CHIMIA)
The confinement of two electrons in each of several non-overlapping spheres is not intended as “Ansatz” for Schrödinger’s equation, and the concomitant kinetic energy is studied. The “ coexistence integral ” of two atomic angular functions is introduced, and the Gillespie description and Pauli exclusion principle are discussed.